Emergence and mechanism of carbapenem-resistant Escherichia coli in Henan, China, 2014 - Wen-juan Liang; Hui-ying Liu; Guang-Cai Duan; Yong-xin Zhao; Shuai-yin Chen; Hai-Yan Yang; Yuan-Lin Xi (Elsevier, 2018)
The emergence and dissemination of carbapenem-resistant Escherichia coli (E. coli) strains is a main risk for global public health, but little is known of carbapenemase producing E. coli in Henan, China. The study was undertaken to investigate the prevalence and mechanism of carbapenem-resistant E. coli strains in a hospital in Xinxiang, Henan, China, 2014. A total of 5 carbapenemase-producing E. coli strains were screened from 1014 isolates. We found that they were all resistant to meropenem and imipenem. Amikacin showed the best sensitivity, with gentamicin coming up next. The positive rate of blaNDM was 80% (4/5). The sequencing results showed that two isolates belonged to blaNDM-1 whereas other 2 isolates carried the blaNDM-5. Other carbapenemase genes including blaIMP, blaVIM, blaKPC and blaOXA-48 were not detected. The blaCTX-M-15, blaTEM-1, sul2, aad, and aac(6")-Ib-cr were also detected. MLST analysis showed that NDM-producing E. coli were sporadic. Conjugation test indicated blaNDM could be transferred. In conclusion, the blaNDM was the principal resistance mechanism of carbapenem-resistant E. coli in the hospital, Henan, China. Keywords: blaNDM, Carbapenem-resistant, Escherichia coli